Zero trust networks with VMware NSX : build highly secure network architectures for your data centers - Keeriyattil, Sreejith (Apress, 2019)
Secure your VMware infrastructure against distrusted networks using VMware NSX. This book shows you why current security firewall architecture cannot protect against new threats to your network and how to build a secure architecture for your data center. Author Sreerjith Keeriyattil teaches you how micro-segmentation can be used to protect east-west traffic. Insight is provided into working with Service Composer and using NSX REST API to automate firewalls. You will analyze flow and security threats to monitor firewalls using VMware Log and see how Packet Flow works with VMware NSX micro-segmentation. The information presented in Zero Trust Networks with VMware NSX allows you to study numerous attack scenarios and strategies to stop these attacks, and know how VMware Air Watch can further improve your architecture. You will: Know how micro-segmentation works and its benefits Implement VMware-distributed firewalls Automate security policies Integrate IPS/IDS with VMware NSX Analyze your firewall's configurations, rules, and policies.